Hong Kong medical journal = Xianggang yi xue za zhi - Hong Kong Academy of Medicine; Hong Kong Medical Association (Hong Kong Academy of Medicine : Hong Kong Medical Association, 1995)
Formerly the Journal of the Hong Kong Medical Association, this peer-reviewed, quarterly journal features general medical research and seminar articles, review articles, medical practice papers, case reports, book reviews, and other materials on a wide scope of topics relating to clinical practice and research in all branches of medicine.
Keywords: Hong Kong Medical Association : Periodicals; Clinical medicine : Periodicals; Medicine : Periodicals; Medicine : China : Hong Kong : Periodicals; Public health : China : Hong Kong : Periodicals; Medicine; Public Health; Clinical medicine; Medicine; Public health; Hong Kong; China; China : Hong Kong